Cover Picture: Photoreduction of Shewanella oneidensis Extracellular Cytochromes by Organic Chromophores and Dye‐Sensitized TiO2 (ChemBioChem 24/2016). (15th November 2016) - Ainsworth, Emma V.; Lockwood, Colin W. J.; White, Gaye F.; Hwang, Ee Taek; Sakai, Tsubasa; Gross, Manuela A.; Richardson, David J.; Clarke, Thomas A.; Jeuken, Lars J. C.; Reisner, Erwin; Butt, Julea N.
Abstract : The cover picture shows the photoreduction of electrically conductive proteins spanning a bacterial outer membrane. The authors show that abiotic and cell‐secreted photosensitizers drive the photocatalytic reduction of extracellular cytochromes. Their studies suggest how photoenergized electrons may be delivered to the interior of non‐photosynthetic micro‐organisms for the synthesis of solar chemicals. More information can be found in the full paper by L. J. C. Jeuken, E. Reisner, J. N. Butt et al. onpage 2324 in Issue 24, 2016 (DOI:10.1002/cbic.201600339 ).